Eclipse Application Programming Interfaces: - Kawuma, Simon; Bamutura, David Sabiiti; Obbo, Aggrey; Mabirizi, Vicent; Kabarungi, Moreen; Nabaasa, Evarist (VFAST Transactions on Software Engineering, 2025)
Eclipse Framework provides stable public APIs and unstable internal APIs. However, there is no guarantee that these interfaces are well tested because several bugs are reportedby interface users on Bugzilla-based Eclipse project. Applications that use buggy APIs risk failing if bugs are not fixed. Bug fixation and resolution takes at least 3 years thus API users have to fix the bugs themselves or abandon that particular API. The study aimed at identifying bug free interfaces in the Eclipse Framework and recommend them to application developers. In this research study, we used both SonarQube and SpotBugs static analysis tools to carry out an empirical investigation on 28 major Eclipse releases to establish the existence of bug free interfaces. We provide a dataset of 218K and 303K bug-free public API and internal API respectively. There exist over $85.9%$ and $88.2%$ bug-free public APIs and internal APIs, respectively, in Eclipse releases. Furthermore, over 80.8% and 44.2% are major and malicious code vulnerability bugs respectively and the average bug remediation effort is 105 days. Results from this study can be used by both interface providers and users as a starting point to know tested interfaces and also estimate efforts needed to fix bugs and an online dataset of bug-free interface is available on Github for developer.